Pengaruh Realisasi Penerimaan Dan Intensifikasi Pajak Kendaraan Bermotor Terhadap Potensi Pendapatan Asli Daerah Dengan Jumlah Kendaraan Bermotor Sebagai Variabel Moderasi Di Bapenda Provinsi Kalimantan Utara - Rika Bulan Karolin; Mohammad Nur Utomo; Rini Yayuk Priyati (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The aim of this research is to examine the effect of realization of PKB revenues and intensification on PAD Potential in BAPENDA of North Kalimantan Province with the Number of Motorized Vehicles as a moderating variable. The type of research used in the research is quantitative research with data in the form of annual Motor Vehicle Tax Reports taken from 5 districts/cities in North Kalimantan, from 2017 to 2021. Data analysis in this research uses Partial Least Squares (PLS)-Structural Equation Modeling (SEM). The research results found that the realization of Motor Vehicle Tax Revenue had a positive and significant effect on the Potential of Original Regional Income in BAPENDA, North Kalimantan Province. This means that the higher the realization of motor vehicle tax revenue, the potential for local revenue in BAPENDA North Kalimantan Province will increase. Intensification of Motor Vehicle Taxes has no effect on the Regional Original Income Potential in BAPENDA of North Kalimantan Province. This means that the higher or lower the level of motor vehicle tax intensification does not have a significant influence on increasing or decreasing the potential for local original income in BAPENDA of North Kalimantan Province. The number of motorized vehicles is unable to moderate the influence of actual motor vehicle tax revenue on the potential for local revenue in BAPENDA, North Kalimantan Province. This means that an increase or decrease in the number of motorized vehicles does not affect the strength or weakness of the realization of motor vehicle tax revenue on the potential for local revenue in BAPENDA of North Kalimantan Province. The number of motor vehicles is able to moderate the influence of motor vehicle tax intensification on the potential for local revenue in BAPENDA, North Kalimantan Province. This means that the increasing number of motorized vehicles can strengthen the influence of motor vehicle tax intensification on the potential for local revenue in BAPENDA, North Kalimantan Province.